LMTdb: A comprehensive transcriptome database for climate-resilient, nutritionally rich little millet (Panicum sumatrense) - Shekhar, Shweta; Prasad, Archana S.; Banjare, Kalpana; Kaushik, Abhijeet; Mannade, Ajit K.; Dubey, Mahima; Patil, Arun; Premi, Vinay; Vishwakarma, Ashish K.; Sao, Abhinav; Saxena, Ravi R.; Dubey, Amit; et al. (Frontiers in Plant Science, 2023)
Little millet (Panicum sumatrense) a native of Chhattisgarh, belongs to the minor millet group and is primarily known as a climate-resilient and nutritionally rich crop. However, due to the lack of enough Omics studies on the crop, the scientific community has largely remained unaware of the potential of this crop, resulting in less scope for its utilization in crop improvement programs. Looking at global warming, erratic climate change, nutritional security, and limited genetic information available, the Little Millet Transcriptome Database (LMTdb) (https://igkv.ac.in/xenom/index.aspx) was conceptualized upon completion of the transcriptome sequencing of little millet with the aim of deciphering the genetic signatures of this largely unknown crop. The database was developed with the view of providing information about the most comprehensive part of the genome, the ‘Transcriptome’. The database includes transcriptome sequence information, functional annotation, microsatellite markers, DEGs, and pathway information. The database is a freely available resource that provides breeders and scientists a portal to search, browse, and query data to facilitate functional and applied Omics studies in millet crops.